Integration of religious values in biology learning and its implications for students' environmental awareness - F. Fitriana; Hafnati Rahmatan; E. Evendi; S. Saminan; M. Mentari (University of Muhammadiyah Malang, 2025)
Environmental degradation necessitates educational strategies that not only enhance cognitive understanding but also cultivate students’ spiritual and moral character. This study examines the effect of incorporating religious values into biology instruction on students’ environmental awareness. Employing a descriptive qualitative approach, data were gathered from 123 high school students across four schools in Aceh Province: SMAN 2 Indrajaya, SMAN 2 Seunuddon, SMAN 2 Samalanga, and SMAN 1 Lhokseumawe. The instruments included validated questionnaires and in-depth interviews with randomly selected participants for data triangulation. Findings indicate that integrating religious values—such as faith-based reflections on air pollution, waste-related flooding, and deforestation—positively influences students’ sense of environmental responsibility, care for nature, and consistency in eco-friendly behavior. Interview results further reveal that students feel a stronger obligation to protect the environment when scientific concepts are connected with religious teachings. However, the study also notes that some students still require ongoing habituation and the presence of positive role models to translate values into consistent action. These findings suggest that incorporating religious values into biology instruction provides a promising foundation for promoting environmental awareness and character development. The study recommends continued integration of this approach in both pedagogy and policy to support character-based environmental education.